A game theoretic approach to solve multiple group decision making problems with interval-valued intuitionistic fuzzy decision matrices. Issue 1 (2nd January 2021) - Kumar, Sandeep; Kumar, Mohit
ABSTRACT: The objective of this paper is to develop a two person zero-sum game theoretic solution approach for multiple attribute group decision making (MAGDM) problems under interval-valued intuitionistic fuzzy environment. In this way, a new order function is introduced to defuzzify the interval-valued intuitionistic fuzzy numbers (IVIFNs) and discuss its properties. In complicated and uncertain group decision-making problems, decision makers face a problem for assessing the group weights for alternatives and attributes. In this paper, the weights of present MAGDM problem with interval-valued intuitionistic fuzzy decision matrices (matrices in which entries are represented by IVIFNs) are calculated by converting it into a traditional two person zero-sum game problem. Then, the expected score for each alternative is calculated using the optimal solution of this game problem. On the basis of the calculated expected score values, the prespecified alternatives are ranked in order to find the best alternative. The validity and applicability of the developed approach are given by a numerical example.